Rediscovering the intrinsic mechanical properties of bulk nanocrystalline indium arsenide - Li, Shuaiqi; Zhang, Jiawei; Guan, Shixue; Guo, Ruiang; He, Duanwei (Nanoscale, 2023)
Is the inverse Hall-Petch relation in ceramic systems the same as that in metal systems? The premise to explore this subject is the synthesis of a dense bulk nanocrystalline material with clean grain boundaries. By using the reciprocating pressure-induced phase transition (RPPT) technique, compact bulk nanocrystalline indium arsenide (InAs) has been synthesized from a single crystal in a single step, while its grain size is controlled by thermal annealing. The influence of macroscopic stress or surface states on the mechanical characterization has been successfully excluded by combining first-principles calculations and experiments. Unexpectedly, nanoindentation tests show a potential inverse Hall-Petch relation in the bulk InAs with a critical grain size ( D cri ) of 35.93 nm in the experimental scope. Further molecular dynamics investigation confirms the existence of the inverse Hall-Petch relation in the bulk nanocrystalline InAs with D cri = 20.14 nm for the defective polycrystalline structure, with its D cri significantly affected by the intragranular-defect density. The experimental and theoretical conclusions comprehensively reveal the great potential of RPPT in the synthesis and characterization of compact bulk nanocrystalline materials, which provides a novel window to rediscover their intrinsic mechanical properties, for instance, the inverse Hall-Petch relation of bulk nanocrystalline InAs. The inverse Hall-Petch effect is observed in a bulk nanostructured material synthesized in one step using the reciprocating pressure-induced phase transition technique. Molecular dynamics simulation provides further evidence of its existence in InAs.